Responsibility of The Government of The City of Banda Aceh in Facilitating Medical Waste Management - Alifa Nisrina; Efendi Efendi (Syiah Kuala Law Journal, 2021)
Article 13 Permenkes No. 18 of 2020 states, Local Governments have the responsibility to facilitate the management of medical waste. In reality, the Banda Aceh City Government has not provided facilitation in the management of medical waste in Banda Aceh City. The purpose of the study was to determine the form of facilitation provided by the Banda Aceh City Government and the policies taken in the management of medical waste. The main data of this study is secondary data and is supported by primary data. Secondary data was obtained from legislation, scientific journals and books, while primary data was obtained through interviews. The results showed that the facilitation provided by the Banda Aceh City Government was only in the form of socialization and advocacy to cross-sectors and monitoring and evaluation of Health Service Facilities. The medical waste management facilitation policy has not been implemented in accordance with the Minister of Health Regulation No. 18 of 2020 and the Banda Aceh City Sanitation Strategy 2010-2025.